Bone tissue material properties are altered during osteoporosis - Prendergast, Patrick John (Hylonome, 2005)
Measurement of the effects of osteoporosis on the mechanical behavior of bone has been performed using whole bone testing, or testing of volumes of ovariectomized cancellous bone1-3 and these studies revealed a decrease in macro-level bone strength. However, it is not clear whether these changes were due only to the reduction in bone mass or whether a reduction in tissue strength also contributed. A number of studies report that the mineral content is unchanged or slightly lower in the osteoporotic bone tissue4 or that there is an increase in the mineral content and a lack of collagen5-7. Such microstructural changes suggest that a corresponding change in the mechanical behavior of the tissue should ensue during osteoporosis. However, to date, the tissue level properties and tissue level mineral content of osteoporotic trabecular bone have never been measured and so such ideas remain conjecture.
PUBLISHED
Keywords: Bioengineering